2020
DOI: 10.1111/geb.13122
|View full text |Cite
|
Sign up to set email alerts
|

Wealth, water and wildlife: Landscape aridity intensifies the urban luxury effect

Abstract: Aim: Urban biodiversity, and its associated ecosystem services, is an important component of the quality of life of urban residents. The "luxury effect" posits a positive association between biodiversity and socioeconomic status in urban areas, and is thus reflective of environmental injustice, as the benefits associated with biodiversity are not equitably shared across society. We aimed to determine the generality of the luxury effect, and to identify the factors causing its variation across published studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 57 publications
0
27
1
2
Order By: Relevance
“…For example, a worldwide study on the impact of urbanisation on avian functional diversity showed 20% less functional diversity on average in urban areas than surrounding natural habitats (Sol et al 2020). However, most research is conducted in the Global North, and conclusions might not always apply to Africa, which is characterised by developing countries with strong socio-economic and socio-cultural gradients, as well as a more tropical climate and different time and pace of urbanisation scenarios (Gupta 2002;Seto et al 2010;McHale et al 2013;Chamberlain et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a worldwide study on the impact of urbanisation on avian functional diversity showed 20% less functional diversity on average in urban areas than surrounding natural habitats (Sol et al 2020). However, most research is conducted in the Global North, and conclusions might not always apply to Africa, which is characterised by developing countries with strong socio-economic and socio-cultural gradients, as well as a more tropical climate and different time and pace of urbanisation scenarios (Gupta 2002;Seto et al 2010;McHale et al 2013;Chamberlain et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This feeds into the globally observed trend of a decline in species diversity as the amount of urban land cover increases across landscapes (Batáry et al 2018). This general pattern is also seen in bird communities of developing countries (van Rensburg et al 2009;MacGregor-Fors and Schondube 2011;Silva et al 2015;Chamberlain et al 2018), although some notable exceptions arise depending on the quality of the surrounding natural (rural) vegetation type and water availability (Dures and Cumming 2010;Chamberlain et al 2020). Unfortunately, it is difficult to ascribe causality to the variety of different ecological and environmental factors that are affecting bird diversity across our urbanrural gradient.…”
Section: Species Richness and Diversitymentioning
confidence: 92%
“…Given that Africa's population is the fastest growing in the world and expected to increase from the current 1.2 billion people to >1.8 billion by 2035 (Institute for Security Studies 2020), there is growing need to focus on biodiversity in these rapidly urbanising African landscapes (Magle et al 2012). Additionally, in Africa, which is characterised by developing countries with strong socio-economic gradients, as well as a more tropical climate and uniquely structured cityscapes, we expect that urban influences on biodiversity will be markedly different to what is known from cities of the Global North (Becker and Morrison 1988;Gupta 2002;Seto et al 2010;McHale et al 2013;Chamberlain et al 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The luxury effect predicts a positive relationship between human wealth and biodiversity. This is supposedly amplified in arid cities (Chamberlain et al 2020), as neighbourhoods age, and might be reduced in tropical areas (Leong et al 2018). Also these findings highlight the need for research in more tropical cities to unravel global patterns.…”
Section: Guest Editorial a Southern Perspective On Urban Birdsmentioning
confidence: 94%